Textual Features of the Epic “Hayrat-ul abror”: Fitur Tekstual dari Epik “Hayrat-ul abror” - Murodova Gulchehra Azamat (Universitas Muhammadiyah Sidoarjo, 2022)
A lot of work has been done to study and publish the works of Alisher Navoi, a great artist. In addition, the poet's epic